Consumer Attitudes towards Indigenous Visual Arts Patronage among the Nanumba of Northern Ghana - Boham, Margaret Araba; Rashid, Mohammed Abubakari (International Journal of Culture and History, 2024)
Research has suggested that many Ghanaians have developed a taste for foreign goods, sometimes leading to the neglect of their made-in-Ghana equivalents. Experts say the consumption of locally made products is a sure way of improving the economic fortunes of the country while preserving the culture of the people. This study sought to investigate the patronage of indigenous visual art forms among the Nanumba of Ghana. It adopted a mixed method approach; using both the qualitative field study and, quantitative descriptive research design. Based on an urban population of 57,587 a sample size of 200 was selected for the study. Interviews, observations, and questionnaires were used as data collection instruments. Findings from the study are presented using both the narrative research analysis and descriptive analysis approaches. The findings showed that many people still patronised the indigenous arts, although some products had seen a major decline in patronage due to factors like modernisation, convenience, superstition, and quality. Recommendations were made to support local artists and artisans and also to encourage the use of local artefacts to preserve the cultural heritage of the people and to promote economic development.